2020
DOI: 10.1002/pat.5136
|View full text |Cite
|
Sign up to set email alerts
|

Study of highly porous poly‐l‐lactide‐based composites with chitosan and collagen

Abstract: Increased interest in the field of tissue engineering promotes the development of biomaterial design. Aspiration to reconstruct native extracellular matrix architecture (ECM) expands the number of applying approaches in polymer scaffold development. In the present work, we proposed a combination of electrospinning and lyophilization techniques to produce materials with ECM‐like morphology based on poly‐l‐lactide fiber matrix with natural bio‐adequate fillers (collagen and chitosan). Morphology, mechanical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Further research on the use of biopolymer blends for packaging material showed poor mechanical properties. Biopolymers such as polylactic acid, chitosan, cellulose have been reported to have low mechanical properties [ 6 ]. This has discouraged their use for many applications such as automobile parts and aerospace.…”
Section: Introductionmentioning
confidence: 99%
“…Further research on the use of biopolymer blends for packaging material showed poor mechanical properties. Biopolymers such as polylactic acid, chitosan, cellulose have been reported to have low mechanical properties [ 6 ]. This has discouraged their use for many applications such as automobile parts and aerospace.…”
Section: Introductionmentioning
confidence: 99%
“…PLA and CNF are having the challenge of agglomeration, which has resulted in low mechanical properties of its composite film. The amphiphilic properties of chitosan were used as a compatibilizer between PLA and CNF in this study 28,36 . In this study, amphiphilic chitosan was prepared and used to enhance polylactic acid's miscibility and properties between PLA and cellulose nanofiber.…”
Section: Introductionmentioning
confidence: 99%